Fatigue index and anaerobic power obtained in different surfaces types - Romário dos Santos, W.; Dechechi, C. J.; Ferreira da Silva, I. A.; Machado Gomes, M.; Fernandes Correia, G. A.; Pinheiro Paes, P.; dos Santos, W. R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
Due to the high intensity of competitive sports, the anaerobic power is a very important physical capacity for most sports. However, the diverse surfaces were these sports may interfere in the performance of this capacity. In running-based sports, the Running Anaerobic Sprint Test - RAST is largely used to evaluate anaerobic power. Considering the specificity of each sport, it is suggested to apply this test on the surface that it is played. Thus, the aim of the present study is to analyze the performance of RAST on different surfaces. The sample was composed by 10 subjects, mean age 20.2 ± 0.9 years old, mean height 1.8 ± 0.1 meters, mean body weight 77.4 ± 15.9 kg, and practice time of 6.0 ± 2.0 years. RAST was conducted on three different surfaces (hard, grass and sand). The maximum and minimum power and the fatigue index were compared between the surfaces. The results indicate that maximum and minimum power were lower in sand when compared to grass and hard surfaces. However, the fatigue index did not change. So, we observed that the surface is an important factor in RAST performance.